The isolated H4-H5 cytoplasmic loop of Na,K-ATPase overexpressed in Escherichia coli retains its ability to bind ATP - Obsil, T; Mérola, F; Lewit-Bentley, A; Amler, E (FEBS letters, 1998)
The H4-H5 loop of the alpha-subunit of mouse brain Na,K-ATPase was expressed and isolated from Escherichia coli cells. Using fluorescence analogues of ATP, this loop was shown to retain its capability to bind ATP. Isolation of a soluble H4-H5 loop with the native ATP binding site is a crucial step for detailed studies of the molecular mechanism of ATP binding and utilisation.
Keywords: Animals; Sodium-Potassium-Exchanging ATPase; Ethenoadenosine Triphosphate; Protein Structure, Tertiary; Escherichia coli; vazebná místa; Recombinant Fusion Proteins; vazba proteinů; terciární struktura proteinů; rekombinantní fúzní proteiny; Mice; adenosintrifosfát; mozek; myši; peptidové fragmenty; ethenoadenosintrifosfát; genetické vektory; cytoplazma; Adenosine Triphosphate; Peptide Fragments; Brain; Cytoplasm; zvířata; Genetic Vectors; Protein Binding; sodíko-draslíková ATPasa; Binding Sites